Sudden unexpected death in epilepsy: A bibliometric overview - Tong, Fang; Lin, Jian; Zeng, Zixuan; Wang, Qi; Yang, Zhifang; Lv, Yehui (Frontiers in Neurology, 2023)
The mechanism of sudden unexpected death in epilepsy (SUDEP) is elusive and many questions remain unanswered. Autopsy is generally unhelpful in providing evidence for the cause of death, as pathological changes may be on the molecular level. Although histopathological examination occasionally demonstrates pathology such as vascular malformation, old traumatic injury, and tumor, in most cases of SUDEP, the examination is negative. We examined the current status of SUDEP research by performing a bibliometric analysis of studies in the Web of Science Core Collection database published between 2002 and 2022. Our aim was to demonstrate areas of interest and frontiers of SUDEP research. A total of 1803 papers were included in the analysis. The number of published papers focused on SUDEP has been increasing since 2002. Main areas of interest include clinical manifestations, prevalence, treatment, and underlying mechanisms. Research teams from the United States and Europe are leading the way in SUDEP research, while Asia trails behind. Future studies regarding the mechanism and neuropathology of SUDEP are warranted.